Dimensions of Service Quality and their Effects on Achieving Competitive Advantage: An Exploratory Study of Banking Organizations in Sulaimaniyah City-Iraq - Said Rashid, Kochar Taher; Answer Ismael, Darbaz; Othman, Bestoon; Ali, Raman (International Journal of Psychosocial Rehabilitation, 2019)
The study purpose is to explore the service quality and its impact on achieving the competitive advantage of the banking organizations in Sulaimaniyah city in Iraq. The sample size of this study is 94 respondents among bank managers and clients of twelve banks in Sulaimaniyah. Descriptive analysis, factor analysis, Spearman correlation, multiple regression analysis, and ANOVA, respectively, were applied to determine the degree of the relationship and prediction of competitive advantage. Findings indicated agreement among the managers and banking clients that banking organizations in Sulaimaniyah adopted banking service quality and its dimensions. The study also found a significant positive relationship between service quality and competitive advantage. Furthermore, the regression analysis outcomes establish that statistically there are significant impacts of banking service quality and all its dimensions towards the competitive advantage.